MANAJEMEN BENCANA BADAN PENANGGULANGAN BENCANA DAERAH DALAM MENANGGULANGI BENCANA BANJIR BANDANG DI KABUPATEN LAHAT - Aqilah, Fatin Nada; Febriyanti, Doris; Amaliatulwalidain, Amaliatulwalidain (ITB AAS Indonesia Surakarta, 2024)
Indonesia is very vulnerable to various types of disasters, including the flash flood disaster experienced by the Lahat Regency. This research aims to determine the disaster mitigation of the Regional Disaster Management Agency (Badan Penanggulangan Bencana Daerah, BPBD) in dealing with flash flood disasters in the Lahat district area. This research used descriptive qualitative methods, with 15 informants. Research data was obtained using interview techniques, observation, and documentation studies so that it could be analyzed using a qualitative data analysis process. This research uses pre-disaster, emergency response, and post-disaster indicators. The research results show that disaster management in Lahat Regency is quite effective in dealing with flash flood disasters. The findings in this research are that even though they have lived in disaster-prone areas for a long time, the community and local government have not demonstrated disaster preparedness, resulting in unavoidable casualties and damage. Therefore, it is necessary to build a better system based on the integration of local wisdom that is adhered to by the local community.